The Effects of Separate Facial Areas on Emotion Recognition in Different Adult Age Groups: A Laboratory and a Naturalistic Study - Faustmann, Larissa L.; Eckhardt, Lara; Hamann, Pauline S.; Altgassen, Mareike (Frontiers in Psychology, 2022)
The identification of facial expressions is critical for social interaction. The ability to recognize facial emotional expressions declines with age. These age effects have been associated with differential age-related looking patterns. The present research project set out to systematically test the role of specific facial areas for emotion recognition across the adult lifespan. Study 1 investigated the impact of displaying only separate facial areas versus the full face on emotion recognition in 127 younger (20-24 years) and middle-aged adults (40- 65 years). Study 2 examined if wearing face masks differentially compromises younger (18- 33 years) versus older adults’ (51- 83 years) emotion recognition in 144 participants. Younger adults outperformed middle-aged adults in the recognition of emotions in Study 1. Overall, participants were better at recognizing emotions when the full face compared to “face sections” was presented. Importantly, older adults identified more emotions from the mouth than the eyes region, while the opposite pattern emerged for younger adults. Similarly, Study 2 observed superior emotion recognition in younger versus older adults. Overall, face masks reduced participants’ emotion recognition; however, there were no differential age effects. Results are discussed in light of current models of age-related changes in emotion recognition.